Formation of secretory granules and mode of secretion in the salivary glands of swiflet - an ultrastructural study - Abu Seman, Ainul Riza (2016)
Two swiftlets species, the Aerodramus fuciphagus and Aerodramus maximus are the only avian species which are known to build their nest from the secretion of their salivary glands. During the breeding season especially during nesting the salivary gland was markedly enlarged and hypertrophied to produce the salivary secretion which hardened to become the nest which is the edible bird nest (EBN).EBN has been reported to be highly nutritious and fortified with immuno competent and antiviral properties. The present study examined this unique gland at the ultrastructural level focusing on the formation of secretory granules and mode of secretion in the salivary gland of A. fuciphagus. The study was also intended to provide some plausible explanation on the origin or source of the immuno-competent and antiviral properties of the EBN. For the above study, samples of swiftlet salivary glands were processed and examined under the transmission electron microscope. Formation of the secretory granules appeared to originate from coalescence of pinched off dilated ends of the rough endoplasmic reticulum. These were carried to the apical cytoplasm where they again coalesced to form larger secretory granules. The content of the secretory granule appeared to be released into the lumen of acinus by rupture of the apical cell membrane which classify the mode of secretion in the salivary gland of the swiftlet as the merocrine type. Ultrastructural evidences indicated that the immuno-competent and antiviral properties of the EBN could be contributed by cytoplasmic ribosomes of the acinar cell.